Thermal degradation kinetics of polyesters containing mesogenic aromatic diols - Mule, Smita Atmaram; Ghadage, R. S.; Jacob, Nalini E.; Rajan, C. R.; Ponrathnam, Surendra (Journal Applied Polymer Science, 2005)
A series of polyesters were synthesized by reacting structurally differing aromatic diols with either saturated (flexible) or unsaturated (rigid) dicarboxylic acid halide by a stirred interfacial polycondensation technique. Thermal degradation kinetics of these polyesters were investigated by applying Coats-Redfern and Horowitz-Metzger nonisothermal procedures. The dynamic thermogravimetry experiments were conducted in nitrogen to obtain differential thermogravimetric plots. Thermal stability of these polyesters was discussed on the basis of semiquantitative methods such as differential procedural decomposition temperature, integral procedural decomposition temperature, and fraction decomposition temperature (e.g., 10 % DT). Degradation proceeded in multiple stages. The thermal degradation patterns and activation energies in these stages were discussed in relation to central bridging moieties of aromatic diol. The activation energies of these polyesters were found to be in the range of 100 to 200 kJ/mol. The effect of spacer type on activation energy was also reported. (c) 2005 Wiley Periodicals, Inc.
Keywords: Activation energy; Degradation; kinetics (polym.); Polycondensation; polyesters

Poly(High Internal Phase Emulsion) of 2-EHA, 2-EHMA and EGDA with naturally occurring phenolic compounds", paper presented at international conference on ?polymers for advanced technology - Ingavle, Ganesh C.; Shaikh, A. A.; Bhongale, Sunil Sitaram; Scaria, S.; Chavan, Nayaku; Qureshi, Mohammed; Ponrathnam, Surendra (Polymers for Advanced Technology, 2006)

Exhaustive analysis of frontal copolymerization of functionalized monovinyl and divinyl monomers - Pujari, Narahari S.; Inamdar, Satish R.; Ambekar, Jalindar D.; Kulkarni, B. D.; Ponrathnam, Surendra (Chemistry-A European Journal, 2007)
A series of copolymers of 2-hydroxyethyl methacrylate (HEMA)/ glycidyl methacrylate (GMA) and ethylene dimethacrylate (EGDM) were synthesized by frontal polymerization (FP). This study was conducted to investigate the effect of crosslink density, type and concentration of initiator, the use of a complex initiator system, porogen, and diluent on the most relevant parameters of FP, such as sustainability of the front, temperature profile, front velocity, and yield. The products were also characterized for intruded pore volume, pore-size distribution, epoxy-functionality number, and surface morphology. Higher crosslink densities (CLDs) and initiator concentration produced higher front velocities, whereas no trend in front temperature was noted. A complex initiation system was effective in stabilizing and increasing the polymerization yield. Relative to suspension polymerization (SP), FP products synthesized without a solvent were microporous, whereas micro-to-macroporous products were obtained in the presence of a solvent (for HEMA-EGDM polymers). We also present, explain, and discuss the exotic patterns observed under a microscope. We observed two basic types of spatial patterns, namely, planar and nonplanar patterns. The type of planar pattern observed under scanning electron microscopy (SEM) has a spatial impulse that appears as a loop followed by regular periodic motion in the radial and axial directions. This behavior gives rise to a repeating pattern that is a few microns thick. Also, nonplanar patterns, namely, layered concentric rings and winding staircase patterns, were observed under SEM.
Keywords: copolymerization; patterns; Polymers; porosity

Low density porous carrier based conceptual drug delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (Microporous and Mesoporous Materials, 2007)
Chronotherapy, a new approach for treating pathological conditions, is based on circadian rhythm. Present work conceptualizes a specific technology, based on combining floating and pulsatile principles to develop drug delivery system, intended for chronotherapy in arthritis. This approach was achieved by using low density microporous polypropylene, Accurel MP 1000 (R), as a multiparticulate carrier along with drug of choice ibuprofen. Carrier amount and solvent volume was kept invariant in designing this simple system by adsorbing drug via melting or solvent evaporation using different carrier: drug ratios. In solvent evaporation, methanol (M) and dichloromethane (DCM) were used. Drug loaded multiparticulate system was subjected to various characterization and evaluation parameters showing influence of adsorption process. Drug release study was performed in acidic environment using pH 1.2 HCl IP medium for 6 h to mimic gastric condition for evaluating gastroretention followed by basic environment using appropriate medium as phosphate buffer pH 7.2 IP for 3 h resembling transit. The release pattern showed influence of drug adsorption methods characterized by ever changing pore geometry with total release ranges in acidic medium as 10.7-27.6% and final release as 55.6-88.6%. Present drug delivery system devoid of any additives/excipients influencing drug release show distinct behaviour from other approaches/technologies in chronotherapy by (a) observing desired low drug release (11%) in acidic medium (b) overcoming the limitations of process variables caused by multiple formulation steps (c) reducing time consumption due to single step process (d) can be extended to controlled release also. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: chronotherapy; floating pulsatile drug delivery; low density porous carrier; melt adsorption; solvent polarity

Low density porous carrier - drug adsorption and release study by response surface methodology using different solvents - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (International Journal of Pharmaceutics, 2007)
Low density porous carriers are widely used in the pharmaceutical applications. Response surface methodology, using 3 2 factorial design was used to study drug adsorption on and its release patterns from microporous polypropylene (Accurel MP 1000((R))) in the absence of additives. Ibuprofen, as model drug, was adsorbed on the polymer by solvent evaporation using two organic solvents methanol (M) and dichloromethane (DCM). The amount of carrier (100 mg) and its particle size range (250-350 mu m) were kept invariant while solvent volume (X-1) and drug amount (X-2) were taken as variables. Drug adsorption pattern depended on the type and amount of solvent used. DSC, XRD, FTIR and TGA, predict crystalline nature and physical form of adsorption. SEM showed the penetration and adsorption of the drug in and on the microporous polymer. Accurel NIP 1000((R)) had a pore volume of 1.992 g/cm(3) and surface area of 55.9855 m(2)/g as detected by mercury porosimetery. On drug adsorption, pore volume ranged from 0.413 to 1.198 g/cm(3) for methanol and 0.280-0.759 g/cm(3) for DCM. Similarly surface area was in the range 38.445-25.497 m(2)/g for methanol and 18.710-32.528 m(2)/g for DCM. The drug release was investigated in phosphate buffer pH 7.2. All batches showed excellent in vitro floating property. Drug release was partial with recovery to complete dependent on type and volume of solvent. R 2 values relating to bulk density, pore volume, surface area and drug release at 60, 120 and 180 min were estimated. Effect of solvent properties shows a positive influence on drug adsorption and release. Release profiles of some batches could be considered as gastroretentive drug delivery system. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 3(2) factorial design; carrier; microporous polymer; Response surface methodology; solvent evaporation

Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Removal of AS(III) and AS (V) from contaminated water sources by sorption onto novel pei-attached poly(hipe) beads", paper presented at international conference on ?role of analytical chemistry in nuclear technology? - Ingavle, Ganesh C.; Tayal, Rajeev; Shaikh, Wasif Abdul Lateef; Chaudhari, Sanjeev; Chavan, Nayaku; Rajan, Chelanattukizhakkemadath Raman; Ponrathnam, Surendra (Role of Analytical Chemistry in Nuclear Technology, 2007)

Water-triggered frontal polymerization - Pujari, Narahari S.; Inamdar, Satish R.; Ponrathnam, Surendra; Kulkarni, Bhaskar D. (Macromolecular Rapid Communications, 2007)
A totally new mode of frontal polymerization (FP) of acrylamide is established which is triggered by the simple addition of a minute, specific volume of water. Experimental conditions under which this mode of polymerization yields linear and water-soluble polyacrylamide were carefully established, paving the way to synthesize commercially pertinent homo- and copolymers. A new redox couple was identified to circumvent the imidization and the ensuing gelation, hitherto associated with FP of acrylamide. Effects of reaction variables such as type and concentration of redox couple and volume of water on measurable parameters of FP such as front velocity, front temperature, shape of front and yield have been studied. Two types of redox couples are reported. Nonplanar frontal regime was observed in few redox couples. We could visually observe helical patterns with naked eyes, while layered patterns were observable under SEM. Additionally, micro-phase separation and heterogeneity in the polymer matrix was observed due to unreacted pockets of monomer which evolve via bulk mode. This nonlinear phenomenon is described.

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity

Novel/conceptual floating pulsatile system using high internal phase emulsion based porous material intended for chronotherapy - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Benson, James R.; Li, Nai-Hong; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The aim of the present study was to design a novel/conceptual delivery system using ibuprofen, anticipated for chronotherapy in arthritis with porous material to overcome the formulation limits (multiple steps, polymers, excipients) and to optimize drug loading for a desired release profile suitable for in vitro investigations. The objective of this delivery system lies in the availability of maximum drug amount for absorption in the wee hours as recommended. Drug loading using 3(2) factorial design on porous carrier, synthesized by high internal phase emulsion technique using styrene and divinylbenzene, was done via solvent evaporation using methanol and dichloromethane. The system was evaluated in vitro for drug loading, encapsulation efficiency, and surface characterization by scanning electron, atomic force microscopy, and customized drug release study. This study examined critical parameters such as solvent volume, drug amount, and solvent polarity on investigations related to drug adsorption and release mostly favoring low-polarity solvent dichloromethane. Overall release in all batches ranged 0.98-52% in acidic medium and 71-94% in basic medium. These results exhibit uniqueness in achieving the least drug release of 0.98%, an ideal one, without using any release modifiers, making it distinct from other approaches/technologies for time and controlled release and for chronotherapy.
Keywords: chronotherapy; floating pulsatile drug delivery system; high internal phase emulsion; ibuprofen; multiparticulate porous carriers

Transfer of technology (ToT) document of polyimide binder resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan. N. N.; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhansekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (2009)

Vinyl-2-pyrrolidone derivatized guar gum based aqueous two-phase system - Kautharapu, Kumar; Pujari, Narahari S.; Golegaonkar, Sandeep B.; Ponrathnam, Surendra; Nene, Sanjay N.; Bhatnagar, D. (Separation and Purification Technology, 2009)
Aqueous two-phase systems (ATPs) are formed when certain combinations of two polymers or polymer and salt are added to water. Phase separation occurs at certain specific concentrations that have similar densities and low interfacial tensions. The present study involves synthesis and application of a novel derivatized guar in aqueous two-phase system. The derivation of guar gum was performed by grafting of 1-vinyl-2-pyrrolidone by a redox reaction in aqueous medium ceric ammonium nitrate (CAN) and potassium Peroxydisulfate(K2S2O8). The ratio of grafting efficiency (%GE) and ratio of grafting (%G) was 56% and 70.1% respectively. The grafted copolymers were characterized for percent yield and FTIR absorbance. A new aqueous two-phase extraction protocol was established using a mixture of derivatized guar and dextran. A phase diagram was constructed based on the phase separation exhibited by the system at 25 degrees C. The partition coefficient was determined for standard bovine serum albumin (BSA), lactate oxidase (LO) and phytase. The partitioning coefficients were 0.479, 1.981, and 2.586 respectively in the Dextran (2 mill ion)/V-GG/H2O system. The influence of an ionic salt sodium chloride (NaCl) was investigated on the partitioning of BSA. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aqueous two phase; graft copolymers; Guar gum; Partition coefficient (K); Phase diagram; Vinyl pyrrolidone; viscosity

Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Amino-phenol-formaldehyde resins by in-situ generation of catalyst - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Beaded cross linked polymers containing tert-amino functional group moities - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Process for synthesis of beaded cross linked polymers, water-in-oil-in-water emulsions and post functionalisation - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Enzyme immobilization on epoxy supports in reverse micellar media: prevention of enzyme denaturation - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Yalangi; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Journal of Molecular Catalysis B-Enzymatic, 2012)
Immobilization of enzymes such as alpha-chymotrypsin (EC 3.4.21.1), yeast alcohol dehydrogenase (YADH) from Saccharomyces cerevisiae (EC 1.1.1.1) and glucose dehydrogenase (GDH) from Gluconobacter cerinus (EC 1.1.1.119) has been carried out. Copolymers of allyl glycidyl ether (AGE) crosslinked with 25% ethylene glycol dimethacrylate (EGDM) (25 mg, dry wt) were contacted with the enzymes solubilized in reverse micellar media (0.5-5 mg/mL)(overall) of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) salt in isooctane, and cetyl trimethylammonium bromide (CTAB) in chloroform-isooctane (50:50, v/v). Although the enzymes are readily denatured (>90%) after adsorption on the copolymer in aqueous buffers, no such adsorption-induced denaturation takes place in reverse micelles. alpha-Chymotrypsin is remarkably stable in AOT reverse micelles when 0.025 M citrate buffer of pH 9.0 containing 2 mM CaCl2 is used in the water pools instead of Tris-HCl buffer of pH 8.5. It was possible to achieve enzyme concentration of 5 mg/mL in 0.3 M AOT at molar ratio of water to surfactant, (W-0), 30 and to obtain alpha-chymotrypsin loading of 20 mg/g of copolymer. The recovered enzyme solution can be reused with a fresh batch of polymer after supplementing the depleted solution. The immobilized enzyme exhibits excellent stability in aqueous buffers at room temperature and can be recycled several times. YADH is stable in both AOT and CTAB reverse micelles while GDH is stable only in CTAB reverse micelles containing 0.05 M Tris-HCI buffer of pH 8.5. Interestingly, the combination of YADH (2.5 mg/g) and GDH (0.5 mg/g) co-immobilized on the copolymer using CTAB-chloroform-isooctane system can be used for regeneration and recycle of NADPH at least 50 times as exemplified by complete reduction of a prochiral ketoester, ethyl 4-phenyl-2,4-dioxobutyrate (10 mM) to ethyl (R)-2-hydroxy-4-phenylbutyrate (HPB ester) using NADPH (0.2 mM). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: allyl glycidyl ether; alpha-Chymotrypsin; ethylene glycol dimethacrylate; Glucose dehydrogenase; Reverse micelles; Yeast alcohol dehydrogenase

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Immobilization of enantioselective lipase on soluble supports for kinetic resolution of drug intermediates - Chaubey, Asha; Parshad, Rajinder; Taneja, Subhash C.; Deokar, Sarika Babasaheb; Raman, Rajan C.; Ponrathnam, Surendra (Journal of Bioactive and Compatible Polymers, 2012)
The microbial lipase, Arthrobacter sp. lipase (MTCC 5125), from the Indian Institute of Integrative Medicine repository, is known as an effective catalyst for high enantioselective kinetic resolution of drug intermediates. The ABL was immobilized on water-soluble linear supports by covalently binding it to the epoxy groups on the N-vinyl pyrrolidone/allyl glycidyl ether and N-vinyl pyrrolidone/glycidyl methacrylate copolymers. The immobilized lipase, on different soluble supports, had 90-110 mg/g protein binding and 500-700 U/g hydrolysis activities for tributyrin substrate. These copolymers had soluble/insoluble characteristics in different pH ranges, which is an advantage over insoluble copolymers. A soluble polymer at neutral pH provided better accessibility to the immobilized enzyme, which was recovered by precipitation at pH 2-3 for reuse. Kinetic resolution of racemic acyl derivatives of chiral auxiliaries and drug intermediates, namely, phenyl ethanol, aminoalcohol, and fluoxetine intermediate resulted in a significant enhancement in enantioselectivity (99%).
Keywords: Arthrobacter sp lipase; Enantioselectivity; Immobilization; Kinetic resolution; N-vinylpyrrolidone; soluble polymer

Co-immobilized glucose oxidase and beta-galactosidase on bovine serum albumin coated allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer as a biosensor for lactose determination in milk - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Ponrathnam, Surendra (Enzyme and Microbial Technology, 2014)
Bovine serum albumin (BSA) was adsorbed on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) at pH 8.0 (16% w/w). The amino, thiol and carboxylic acid functional groups available on protein coated surface were utilized for covalent immobilization of glucose oxidase and beta-galactosidase, both independently, and in a step-wise manner on the same matrix, with no more than 10% loss of enzyme activity during immobilization. Glutaraldehyde cross-linking after immobilization provided stable enzyme preparations. The pH-optima of the immobilized enzymes were similar to those for free enzyme but their thermal stability was vastly improved. The co-immobilized enzyme support was used as a biosensor for determination of lactose in milk with excellent reproducibility and reusability. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: beta-Galactosidase; Bovine serum albumin; Glucose oxidase; Immobilization; Lactose assay

Comparison of polymer induced and solvent induced trypsin denaturation: the role of hydrophobicity - Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2014)
Trypsin adsorption from aqueous buffer by various copolymers of allyl glycidyl ether-ethylene glycol dimethacrylate (AGE-EGDM) copolymer with varying crosslink density increases with increasing crosslink density and the effect slowly wears off after reaching a plateau at 50% crosslink density. The copolymer with 25% crosslink density was reacted with different amines with alkyl/aryl side chains to obtain a series of copolymers with 1,2-amino alcohol functional groups and varying hydrophobicity. Trypsin binding capacity again increases with hydrophobicity of the reacting amine and a good correlation between logP(octanol) of the amine and protein binding is observed. The bound trypsin is denatured to the extent of 90% in spite of the presence of hydrophilic hydroxyl and amino groups. The behavior was comparable to that in mixtures of aqueous buffer and water-miscible organic co-solvents where the solvent concentration required to deactivate 50% of the enzyme (C-50) is dependent on logP(octanol) of the co-solvent. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Denaturation; Hydrophobicity; Polymer; Trypsin

Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin

Synthesis and characterization of hypercrosslinked hydroxyl functionalized co-polymer beads - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (European Polymer Journal, 2014)
Hydroxyl functionalized beaded copolymers were synthesized from 2-hydroxy ethyl methacrylate by suspension polymerization using two different crosslinking agents (EDMA, DVB) and diluents (1,1,2,2-tetrachloroethane, 1,2-dichlorobenzene). Microporous beads with high surface area were successfully synthesized and characterized by different techniques. Maximum surface area obtained was 564 m(2)/g bearing uniform, spherical as well as non-aggregation images of beads. Thermal properties such as DTG and DSC reveal that, type of crosslinker (flexible/rigid) is major while its concentration is minor parameter that affect decomposition and softening temperature of copolymer. Swelling ratio of copolymer beads was examined as a function of crosslinker and crosslink density. Swelling behavior is in accordance with copolymer-solvent interaction parameter. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Copolymer; Morphology; surface area; Suspension polymerization; Swelling ratio

Design and synthesis of cauliflower-shaped hydroxyl functionalized core-shell polymer - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Designed Monomers and Polymers, 2015)
Conventional crosslinked polymers and homopolymers both have their own limitations. As a result, core-shell polymer was synthesized to obtain cauliflower-shaped and highly hydroxyl functionalized polymer. For the core, acrylate-based copolymers were synthesized by varying crosslinkers and porogens at different crosslink density. Owing to high surface area (554 m(2)/g), poly(MMA-co-DVB) was used as a core and low-molecular weight (24,600g/mol) poly(GMA) was used as a shell in core-shell approach. Average particle sizes of the core polymers were in the range of 15-75 mu m. In order to evaluate reactivity efficiency of core-shell polymer, hydroxyl content was evaluated with a value of 3.97mmol/g. Importantly, hydroxyl content demonstrated the successful increase in reactive sites of the core-shell polymer over conventional crosslinked hydroxyl polymer. Notably, synthesized core-shell polymer has more surface area and pore volume which substantially attributes for better polymer efficiency during application. Scanning electron microscopy images revealed the spherical, uniform, and slightly conglomerated properties of core-shell polymer. Due to higher reactivity, insolubility, and more surface area of hydroxyl functionalized core-shell polymer, its use become inevitably essential.
Keywords: C-13 solid state NMR; cauliflower-shaped porous beads; core-shell polymer; hydroxyl functionalization; surface area

Hyperhydrophilic three-dimensional crosslinked beads as an effective drug carrier in acidic medium: adsorption isotherm and kinetics appraisal - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (New Journal of Chemistry, 2015)
Conventional drug delivery materials are known to provide slow and low drug loading in aqueous medium due to the hydrophobic or less hydrophilic properties of the carrier. However, the present study explored the synthesis of cheaply available metals modified with a hyperhydrophilic polymer. Hyperhydrophilic three-dimensional crosslinked beads as a drug carrier were synthesized with desirable properties that substantially influence the polymer efficiency. These synthesized polymers were characterized for surface area, particle size, acid content and morphology, and the metal modification was evaluated to obtain an efficient polymer for drug adsorption in an acidic medium. Contact time, which significantly affects drug adsorption was comparatively evaluated using the cheaply available metals, cobalt and nickel. Interestingly, an adsorption study revealed that gradual drug loading occurs during the initial 12 h. Afterwards, adsorption increases steadily and then stabilizes. Furthermore, theoretical predictions of adsorption, including Langmuir adsorption isotherm and pseudo order kinetics, were also evaluated. Remarkably, polymer supported Co/Ni demonstrated 85 and 78% metoprolol drug adsorption, respectively, at an optimum pH of 3 after 24 h. Langmuir adsorption isotherm revealed monolayer adsorption on the polymer supported Co/Ni. Pseudo first and second order kinetics were also evaluated and demonstrated the adsorption mechanism and equilibrium adsorption capacity, respectively.

Role of interfacial tension of solvating diluents and hydrophilic-hydrophobic cross-linkers in hyper-cross-linked solid supports - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Industrial & Engineering Chemistry Research, 2015)
The properties of a hyper-cross-linked solid support are the outcome Of the interfacial tension created by solvating/nonsolvating diluents, the hydrophilicity/hydrophobicity of the cross-linkers, and their concentrations. Interestingly, a More hydrophobic diluent and cross-linker as well as a higher concentration of cross-linker-containing copolymer revealed an increase In surface area. A high surface area and low cross-link density (CLD) polymer illustrated higher epoxy content. Importantly, maximum surface area (533 m(2)/g) Was obtained at high CLD; inversely, epoxy,content (1.83 mmol/g) was higher at low CLD polymer. Notably, greater rigidity of cross-linker and its higher concentration increased T-max and T-g; contrarily, greater flexibility of cross-linker and its concentration attenuated T-max and T-g. Thermal study demonstrated the thermostability (300 degrees C) and polymer safe temperature (220 degrees C). Indeed, a lower solubility parameter difference between polymer and swelling solvent produces a higher polymer-solvent interaction parameter, resulting in increased polymer swelling. Polymers with high surface area and low CLD demonstrated greater swelling behavior.

Synthesis and characterization of thermotropic liquid crystalline polyimides - Mane, Sachin; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Bulletin of Materials Science, 2015)
Non-symmetrical and linear dyad-based mesogens were synthesised containing imine or ester bridging group. In the present work, due to the absence of branching in diamine-based mesogen, the structure has-rigidity inversely imine/ester bridging groups between two benzene rings imparts-flexible property to the mesogen and consequently rigid-flexible property has been balanced. The synthesised mesogens were characterized by different techniques including nuclear magnetic resonance and Fourier transform infrared spectroscopy. Liquid crystalline polymers (LCPs) were synthesised using pyromellitic dianhydride and 4-[(4-aminobenzylidene)amino]aniline or 4-aminophenyl-4-aminobenzoate. Subsequently, thermotropic liquid crystalline polymers (TLCPs) have also been evaluated to obtain optical microscopy textures at different temperatures which demonstrated interesting and notable changes. It is worth noting that marble-like textures were observed upto 200A degrees C.
Keywords: Diamine; liquid crystalline polymer; mesogen; optical microscopy textures; pyromellitic dianhydride

Crosslinked polymer embedded Cu/Ag for comparative drug adsorption and kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal of Polymeric Materials and Polymeric Biomaterials, 2016)
Two-dimensional crosslinked polymer (2-DCP) was synthesized for evaluation of drug adsorption and kinetics thereof. Further, polymer properties were evaluated and parameters such as contact time and adsorption isotherm were also studied. Herein, contact time demonstrated 83% and 85% of drug loading in an acidic medium for two-dimensional crosslinked polymer embedded copper and silver (2-DCP-Cu/Ag), respectively in 24h. Initial 4h is the exponential drug loading period whereas drug loading was increased gradually after 4h. Salbutamol loading was well-fitted to Langmuir adsorption isotherm, which indicated a monolayer drug adsorption with respect to 2-DCP-Cu/Ag. Pseudo first- and pseudo second-order kinetics was evaluated to perceive the drug adsorption mechanism and equilibrium adsorption capacity. Monolayer drug adsorption with chemisorption mechanism was observed for 2-DCP-Cu/Ag. In addition to this, decomposition temperature of polymer was 440 and 325 degrees C while glass transition temperature of polymer was 280 and 200 degrees C before and after metal modification, respectively. (A=aqueous phase; B=organic phase; C=drug solution; D=drug loaded polymer; E=enlarged drug loaded polymer.) [GRAPHICS] .
Keywords: Adsorption isotherm; adsorption kinetics; crosslink polymer; drug loading; langmuir adsorption isotherm; salbutamol

Interfacial tension approach toward drug loading with two-dimensional crosslinked polymer embedded gold: adsorption kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal Of Polymeric Materials And Polymeric Biomaterials, 2016)
Interfacial tension of drugs with hydrophilic polymer (A) embedded gold resulting into selective drug adsorption, which also affected the drug adsorption kinetics. Two-dimensional crosslinked polymer embedded gold was synthesized for drug loading application in an acidic buffer. Lower interfacial tension of pantoprazole sodium (B) revealed the exponential loading inversely loading was gradual for chloroquine (C) having more interfacial tension with adsorbent. Initial 2 h was the exponential adsorption period for a pantoprazole sodium whereas exponential adsorption begins after 12 h for a chloroquine. Monolayer drug adsorption was obtained because Langmuir adsorption isotherm was obeyed by both drugs. Moreover, pseudo first-and pseudo second-order kinetics was also evaluated which demonstrated that reactive sites of the adsorbent are homogeneous and drug adsorption mechanism is chemisorption and not the physisorption. Thermal analysis was evaluated to confirm the polymer thermostability and glass transition temperature during catalytic applications in thermal reactions.
Keywords: Adsorption isotherm; adsorption kinetics; drug loading; drug polarity; Interfacial tension

Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties

Selective solid-phase extraction of metal for water decontamination - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Applied Polymer Science, 2016)
Metal-contaminated industrial effluent is a major concern for human health. Therefore, the removal of metal is of primary importance. In this study, metals were selectively extracted from water. Selective metal recovery was studied with a crown-ether-based polymer, wherein the selectivity was observed for strontium over lead. Parameters influencing the metal recovery, such as the contact time, adsorbent dosage, and metal-ion concentration, were evaluated. Interestingly, the adsorption rate of strontium was exponentially increased for the initial 4 h, and lead was adsorbed exponentially after 6 h. Notably, 98% strontium adsorption and 64% lead adsorption were obtained in 24 h. The Langmuir adsorption isotherm was in good agreement and demonstrated that the reactive sites of the adsorbent were homogeneous with monolayer metal adsorption with an adsorbent. The Freundlich adsorption isotherm was not obeyed by both metals. The pseudo-first-order and pseudo-second-order kinetics indicated that strontium was adsorbed by chemisorption and lead was adsorbed by physisorption. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42849.
Keywords: Adsorption; copolymers; crosslinking; kinetics; radical polymerization

Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties

One-pot synthesis of bimodal (macro-meso, micro-mesoporous) silica by polyHIPE: parameter studies - Wale, Apparav; Nalawade, Archana; Ponrathnam, Surendra; Rajan, C. R.; Badiger, Manohar (Journal of Porous Materials, 2020)
Porous silica with hierarchical organization of pore structure is desired for a variety of applications such as, chromatography, sensing, control release, scaffold for biomedical applications and catalysis. Highly porous polymers obtained from high internal phase emulsion (HIPE) templating route have attracted increasing attention of researchers due to their hierarchical porous and interconnected structure with high porosity and low density. The novel method adopted in our approach combines redox initiated polymerization using HIPE polymerization and an in-situ sol-gel processing technique followed by calcination to obtain highly porous materials. The obtained materials have reminiscent of polyHIPE morphology containing pores and interconnected pore throats in micrometer size range with mesopores on the wall of macropores. The effect of concentration of TEOS, volume of dispersed phase, crosslinker concentration, shear rate and surfactant concentration as well as variation in calcination temperatures on the properties of silica materials were examined.
Keywords: Mesoporous material; PolyHIPE; Polymer-silica hybrid; Porous silica

Construction of beta-cyclodextrin linked glycidyl methacrylate polymers for stereoselective separation of chiral drug - Wale, Apparav; Mulani, Khudbudin; Deshpande, Supriya; Rajan, C. R.; Ponrathnam, Surendra (Journal of Polymer Research, 2021)
In this present study, a series of cross-linked porous polymers based on Glycidyl Methacrylate (GMA) were synthesized by suspension polymerization using cyclohexanol and hexanol as pore generating solvents. beta-cyclodextrin (beta-CD) was covalently bonded to the polymers by using Hexamethylene Diisocyanate (HMDI) and Sebacoyl Chloride (SC) as spacer arms. The effects of matrix properties such as pore volume, type of crosslinker, and spacer on the loading of beta-cyclodextrin were investigated. The stereoselective binding of enantiomers of the anti-depressant drug citalopram was studied using beta-cyclodextrin loaded polymers under batch adsorption mode. The capacity factor and selectivity of isomers were investigated also. This study reveals that these beta-cyclodextrin bonded Glycidyl Methacrylate (GMA) polymers are potentially suitable for chromatographic separation of citalopram.
Keywords: beta-cyclodextrin; Citalopram; Glycidyl Methacrylate (GMA) beads; HPLC etc; Stereoslelctivity

Highly interconnected porous monolithic and beaded polymers using high internal phase emulsion polymerization: tuning porous architecture through synthesis variables - Ponrathnam, Timothy; Behere, Isha; Ponrathnam, Surendra; Ingavle, Ganesh (Polymer International, 2023)
Open porous polymeric materials have gained popularity due to their exceptional properties and applications in tissue engineering scaffolds, drug delivery, enzyme immobilization and catalysis support. This study developed a novel two-stage approach to create networked, crosslinked poly(2-hydroxyethyl methacrylate-co-N,N'-methylenebisacrylamide) HEMA-MBA beads. The first part involves producing an oil-in-water-in-oil high internal phase emulsion (HIPE). This is followed by suspension polymerization using a redox initiator pair. In this study, a mixed surfactant combination with low and high hydrophilicity-lipophilicity balance surfactants was identified and successfully utilized to prepare a stable oil-in-water-in-oil HIPE. The effect of crosslinker concentration (i.e. crosslink density), surfactant concentration and monomer-to-porogen ratio on pore architecture and surface area were successfully evaluated. In addition, a new protocol was developed to synthesize HEMA-MBA monoliths using an oil-in-water HIPE method at ambient temperature using a redox initiator pair. The effect of crosslink density and oil phase on pore architecture and surface area was evaluated. Key variables affecting the morphology of porous HEMA-MBA beads and monoliths were identified and quantified, allowing future development of porous HEMA-based polymer beads and monoliths with tunable morphologies which are suitable for numerous applications, especially in the biomedical field. (c) 2022 Society of Industrial Chemistry.
Keywords: HIPE polymerization; porosity; porous polymers; redox polymerization; Suspension polymerization

Novel shear thickening fluids possessing high shear rates using monodispersed silica nanoparticles and PEG - Chavan, Nayaku; Dhage, Atul; Wale, Apparav; Thorave, Asmita; Rajdeo, Kishor; Kamble, Sanjay; Ponrathnam, Surendra; Tambe, Sanjeev; Verma, Sanjeevkumar (Polymer Bulletin, 2023)
Higher shear rate possessing homogeneous shear thickening fluids were synthesized using monodispersed silica nanoparticles and polyethylene glycol (PEG). Novel homogeneous methodology was developed for the synthesis of shear thickening fluids using monodispersed silica nanoparticles and PEG. Shear rate of shear thickening fluids (STF) was determined using rheometer at room temperature. The normal shear rate was observed in the range of 100 to 1200 s(-1), whereas higher shear rate 2000 s(-1) was obtained using monodispersed silica nanoparticles, PEG and shear rate enhancer. Monodispersed silica nanoparticles were synthesized in a typical one-pot using modified Stober's method at room temperature. Precursors were used for the synthesis of monodispersed silica nanoparticles such as tetraethyl orthosilicate (TEOS), ethanol, deionized water and ammonia as catalyst. Particle size of monodispersed silica nanoparticles was in the range of 100-1200 nm, and particle size distribution was varied from 0.000 to 0.221. Synthesis of monodispersed silica nanoparticles was studied by various parameters, namely effect of TEOS concentration, grade of ethyl alcohol, ammonia concentration and water concentration. TEOS concentration effect shows particle size and particle size distribution increases with increase in concentration of TEOS. Even though concentration of TEOS was increased up to 5 times the observation was same for all particle sizes such as 100, 300 and 500 nm. Particularly in the case of 300 nm monodispersed silica nanoparticle synthesis, as TEOS concentration was increased from 1 to 5X (5 times) the particle size was increased from 331.7, 447.8, 497.0, 512.0 and 531.7 nm and particle size distribution was 0.005, 0.000, 0.006, 0.007 and 0.089, respectively. The effect of grade of ethyl alcohol illustrates that Indian rectified spirit shows almost similar results with respect to China make ethyl alcohol. Comparative study of China and Indian rectified spirit shows silica nanoparticle size was 174.6 and 174.2 nm, and particle size distribution was 0.065 and 0.071, respectively. Ammonia concentration effect explains particle size and particle size distribution increases with increase in concentration of ammonia. Water concentration effect shows particle size and particle size distribution increases with increase in concentration of ammonia. Comparative data of water concentration effect for 1316 and 1974 mL shows particle size were 321.7 and 488.0 nm, and particle size distribution was 0.083 and 0.05, respectively, under similar conditions. Morphological studies displayed the shape of the silica nanoparticles was spherical, monodispersed and isolated. A typical TEM image of monodispersed silica nanoparticles for 500 nm was observed with extremely low polydispersity, i.e., 0.000. It is very difficult to get such a type of excellent photograph of monodispersity by Stober's method particularly on large scale. Rheology study of homogeneous shear thickening fluids studied by varying the parameters such as composition of silica nanoparticles with PEG, effect of amount of solvent, effect of refluxing time, effect of additive with respect to the mol. wt. of PEG and effect of additive such as Tannin. All these parameters of STF explored with respect to the shear rate and shear viscosity. Effect of ethanol amount on STF demonstrates the shear rate increases with increase in amount of solvent. Effect of refluxing time on STF exhibits the shear rate increases with increase in refluxing time. Effect of composition based on 500 nm monodispersed silica nanoparticles and PEG 200 with respect to 60:40, 65:35 and 70:30 composition was studied and the results predict that shear rate increases with increase in silica percentage in composition, i.e., 118, 265 and 1200 s(-1) for 60:40, 65:35 and 70:30 composition, respectively, whereas maximum viscosity decreases with increase in silica content, i.e., 2.559, 1.420 and 1.200 Pa.s for 60:40, 65:35 and 70:30 composition, respectively. Effect of additive on shear rate and shear viscosity illustrates that shear rate decreases with increase in additive percentage in composition, whereas maximum viscosity increases with increase in additive content. Effect of additives on shear rate and shear viscosity was performed using 65:35 composition with respect to PEG 200 along with PEG 6000 shows shear rate was decreased from 142 to 6.42 s(-1) and maximum viscosity was increased from 56.1 to 571.0 Pa.s when the quantity of PEG 6000 was doubled. In general, additive decreases shear rate and increases shear viscosity (maximum). But effect of Tannin as an additive on 500 nm monodispersed silica nanoparticles with PEG 200 using 70:30 composition showed enormous increase in shear rate, i.e., 2000 s(-1). This is anomalous behavior of additive was observed.
Keywords: Monodispersed silica nanoparticles; Nanocomposite; Polyethylene glycol; Shear rate; Shear thickening fluid